Immunogenicity of an Additional mRNA-1273 SARS-CoV-2 Vaccination in People With HIV With Hyporesponse After Primary Vaccination. (19th November 2022) - Jongkees, Marlou J; Geers, Daryl; Hensley, Kathryn S; Huisman, Wesley; GeurtsvanKessel, Corine H; Bogers, Susanne; Gommers, Lennert; Papageorgiou, Grigorios; Jochems, Simon P; den Hollander, Jan G; Schippers, Emile F; Ammerlaan, Heidi S M; et al.
Abstract: Background: The COVIH study is a prospective coronavirus disease 2019 (COVID-19) vaccination study in 1154 people with HIV (PWH), of whom 14% showed reduced antibody levels after primary vaccination. We evaluated whether an additional vaccination boosts immune responses in these hyporesponders. Methods: The primary end point was the increase in antibodies 28 days after additional mRNA-1273 vaccination. Secondary end points included neutralizing antibodies, S-specific T-cell and B-cell responses, and reactogenicity. Results: Of the 66 participants, 40 previously received 2 doses ChAdOx1-S, 22 received 2 doses BNT162b2, and 4 received a single dose Ad26.COV2.S. The median age was 63 years (interquartile range [IQR], 60–66), 86% were male, and median CD4 + T-cell count was 650/μL (IQR, 423–941). The mean S1-specific antibody level increased from 35 binding antibody units (BAU)/mL (95% confidence interval [CI], 24–46) to 4317 BAU/mL (95% CI, 3275–5360) ( P < .0001). Of all participants, 97% showed an adequate response and the 45 antibody-negative participants all seroconverted. A significant increase in the proportion of PWH with ancestral S-specific CD4 + T cells ( P = .04) and S-specific B cells ( P = .02) was observed. Conclusions: An additional mRNA-1273 vaccination induced a robust serological response in 97% of PWH with a hyporesponse after primary vaccination. Clinical Trials Registration . EUCTR2021-001054-57-N. Abstract : An additional 100 µg mRNA-1273 vaccination substantially increased SARS-CoV-2 S1-specific binding antibody levels in people with HIV with a serological hyporesponse after a primary vaccination regimen. This response was observed regardless of the primary vaccination regimen or patient characteristics.